Rezultati popisa na študentskem biološkem taboru potrjujejo visoko vrstno bogastvo netopirjev (Chiroptera) v jugozahodni Sloveniji - Gojznikar, Jan (Natura Sloveniae, 2025)
Southwestern Slovenia is known for its high bat species richness, since it is locat-ed at the junction of the Submediterranean and Dinaric regions. Sharp transitions between biogeographic entities are also reflected in habitat diversity, which in turn suits multiple species. Between 17th and 23rd July 2022, we surveyed bats in a wider region surrounding Pivka as part of the students’ biological research camp Biocamp 011. Our goal was to visit as many potential bat sites as possi-ble and to contribute to the knowledge of bats in the region. During the day, we surveyed bats at their roosts, while during the night we utilised the mist-netting method. Occasionally, the latter was upgraded with detecting bat echolocation calls. We detected 23 bat species, including some of greater conservational inter-est. We recorded seven Rhinolophus hipposideros nurseries and one nursery of Myotis brandtii. The latter had already been known, however, during our visit we noted a marked increase in present individual count in comparison to previous research. We also more than doubled the number of caught Nyctalus lasiopterusfor Slovenia. The high success when performing mist-nettings is likely due to the extreme drought in the summer of 2022, which forced bats to aggregate near still existing water bodies. High numbers of detected species, which can also be at-tributed to high spatial heterogeneity with marked transition between different habitats, reaffirm high bat species richness of SW Slovenia. We conclude that it is sensible to continue with bat surveys in this species rich area.
Keywords: netopirji; Pivška kotlina; vrstna pestrost; zoologija